Personal Hygiene as Scabies Factors Incidence in the Institute Rehabilitation Center of the Vagrants, Scrounger and Mental Disabilities in South Sumatra Region - Haniifa, Rahmadita Zinda (JURNAL KESEHATAN LINGKUNGAN, 2024)
Introduction: Scabies, caused by the mite Sarcoptes scabiei, is a highly contagious skin infestation. Poor personal hygiene often contributes to its prevalence. This study aims to identify specific aspects of personal hygiene that influence the incidence of scabies among residents of the Institute Rehabilitation Center of The Vagrants, Scroungers, and Individuals with Mental Disabilities in the South Sumatra Region. Methods: This observational-analytic study employed a case-control design. Data collection involved clinical records, observations, and questionnaire-based interviews. A total of 160 occupants, comprising 80 cases and 80 controls, were selected through simple random sampling. Data analysis utilized chi-square test and multiple logistic regression tests. Results and Discussion: Chi-square analysis revealed significant associations (p-value = 0.000) between scabies incidence and bathing habits, cleanliness of mattresses and bed linen, cleanliness of clothing, and open defecation behavior. Multiple logistic regression indicated that open defecation behavior (OR = 56.336; 95% CI = 17.281 – 158.500) was the primary personal hygiene factor influencing scabies incidence. Thus, maintaining proper open defecation practices is crucial for residents' hygiene and health. Conclusion: Poor personal hygiene practices, including inadequate bathing habits, unclean bedding, dirty clothing, and open defecation behavior, contribute to the occurrence of scabies. Effective education and counseling by healthcare professionals are essential for promoting better hygiene practices among residents.